Developing a CLIL textbook evaluation checklist - Beatriz López Medina (Universidad de La Sabana, 2016)
In the last decades, the number of bilingual schools in Europe has increased significantly.Most of these schools implement CLIL methodology in their teachingand, consequently, there is a demand for new and appropriate materials for eachcontent subject taught through a foreign language: new textbooks written in L2are needed, and the existent offer does not meet the current demand. Given thatCLIL materials development is a relatively recent field, there is not much researchon the evaluation of those still insufficient course books. In this paper, and in orderto evaluate CLIL textbooks, we propose a tentative checklist twofold based: onthe one hand, based on previous checklists created to evaluate ELT textbooks - CLILmaterials use principles/techniques of foreign language teaching (Steirt and Masser,2011)-, and, on the other hand, based on the criteria for producing quality CLILlearning materials drawn up by Mehisto (2012). Further research is in process inorder to refine the checklist with the results of an analysis of the criteria carriedout by a focus group of CLIL teachers, and of a survey addressed to teachers whoare currently implementing CLIL in their schools. doi:10.5294/laclil.2016.9.1.7